2015
DOI: 10.1089/scd.2014.0521
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Gene-Modified Mesenchymal Stem Cells Augment Sinonasal Wound Healing

Abstract: This study was designed to investigate the effects of hepatocyte growth factor (HGF) transgenic mesenchymal stem cells (HGF-MSCs) on wound healing in the sinonasal mucosa and nasal epithelial cells (NECs). We also sought to determine whether HGF-MSCs and MSCs can migrate into the injured mucosa and differentiate into ciliated cells. Human HGF-overexpressing umbilical cord MSCs (hHGF-UCMSCs) were established, and upregulation of hHGF expression was confirmed by real-time PCR (RT-PCR) and enzyme-linked immunosor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…This in vitro assay is widely used to study some functional aspects of keratinocytes and fibroblasts in the wound healing process. 36 38 We conducted this experiment to determine whether the immunomodulatory effects of JWH015 on keratinocytes and fibroblasts affect their migration capabilities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This in vitro assay is widely used to study some functional aspects of keratinocytes and fibroblasts in the wound healing process. 36 38 We conducted this experiment to determine whether the immunomodulatory effects of JWH015 on keratinocytes and fibroblasts affect their migration capabilities.…”
Section: Methodsmentioning
confidence: 99%
“…The migration capabilities of these cells to fill the scratch gap mimic a wound healing process. 36 , 37 This process was measured at base line (0 h), and at 4, 12, 17 and 24 h following the scratch. Six digital images (5×) per condition were taken at each time point in the same area, next to a line of reference that was drawn previously.…”
Section: Methodsmentioning
confidence: 99%
“…There is little evidence for the differentiation of UC-MSCs into relevant cells; it may be related to xenogeneic transplantation used in most of the studies. Presently, proposed mechanisms of UC-MSCs therapeutic activity include trophic and paracrine effects on cells of the immune system, remodeling of the extracellular matrix, angiogenesis, apoptosis, and stimulation of the migration and proliferation of resident progenitor cells [ 18 , 19 , 21 29 , 31 , 104 ]. All of the studies show amazing prospects for clinical use of UC-MSCs.…”
Section: Preclinical Studies Regarding the Use Of Uc-mscsmentioning
confidence: 99%
“…Alapure et al found that bone marrow MSCs with incorporated biomaterial covering burn wounds promote closure, reepithelialization, granulation tissue formation, and vascularization of burn wounds [5]. Modification of MSCs by hepatocyte growth factor and vascular endothelial growth factor (VEGF) genes to increase necessary biological effects and augment wound healing has been confirmed [6, 7].…”
Section: Introductionmentioning
confidence: 99%